Pengaruh Tingkat Suku Bunga Dan Perputaran Piutang Terhadap Rentabilitas Pada PT. Bank Negara Indonesia (Persero) Tbk - Madya, Erniwati; toding, selvi (P3M STIEM, 2021)
Abstract: This review intends to decide if loan fees influence benefit, regardless of whether receivable turnover influences productivity, and to decide if financing costs and records receivable turnover at the same time influence profitability.Collecting information utilizing optional information acquired from budget summaries utilizing cross sectional strategies. The populace in this review is the budget summaries of PT Bank Negara Indonesia Tbk. The time frame 2011 - 2020 while the examples taken added up to 40 examples. The consequences of the fiscal reports have been tried with the traditional supposition test as ordinariness suspicion, multicollinearity presumption, autocorrelation presumption and heteroscedasticity presumption. Strategies for information investigation utilizing different straight relapse examination techniques.The results showed that the primary loan cost had a positive and irrelevant impact on productivity. The two records receivable turnover have a positive and critical impact on productivity. Third, loan costs and records receivable turnover simultaneously affect benefit.